2013
DOI: 10.1038/eye.2012.300
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of a customized toric intraocular lens for correction of post-keratoplasty astigmatism

Abstract: Purpose To report visual and refractive outcomes, and endothelial cell loss following primary and secondary 'piggyback' toric intraocular lens (IOL) implantation in patients with high post-penetrating keratoplasty (PK) astigmatism. Methods Prospective case series. Nine eyes of nine patients with post-PK astigmatism were consecutively recruited for implantation of a customized toric IOL. Six underwent simultaneous phacoemulsification (PE) and three pseudophakic eyes had a secondary 'piggyback' toric IOL implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 20 publications
(30 reference statements)
1
30
1
Order By: Relevance
“…Toric intraocular lens implantation (phakic or pseudophakic) provides a wider range of correction but lens rotation, increased endothelial cell loss, corneal decompensation, graft rejection, endophthalmitis, and secondary glaucoma are important drawbacks of such procedures [ 27 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Toric intraocular lens implantation (phakic or pseudophakic) provides a wider range of correction but lens rotation, increased endothelial cell loss, corneal decompensation, graft rejection, endophthalmitis, and secondary glaucoma are important drawbacks of such procedures [ 27 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many small studies about implantation of toric IOLs can be found in the literature with excellent results, as observed by Stewart and McAlister [ 4 ], Srinivasan et al [ 5 ], Wade et al [ 6 ], and Muftuoglu et al [ 7 ]. Overall, the endothelial cell loss is between 5 and 10% and the IOL stability is excellent [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 94%
“…Excellent results can be obtained by secondary sulcus implantation of piggyback toric IOLs in pseudophakic eyes [ 5 , 9 ]. Meyer and McGhee [ 9 ] demonstrated an uncorrected distance visual acuity changing from 1.2 to 0.3 after a year of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…There are relatively few published reports on the use of a secondary sulcus lens for the treatment of postkeratoplasty refractive errors, mainly limited to a few cases 11,14 and a case series. 18 A recent series described favorable results with a 3-piece "additive" sulcus lens for patients with previous keratoplasty and high astigmatism, although 2 eyes developed corneal edema requiring repeat keratoplasty.…”
Section: Discussionmentioning
confidence: 98%